2012
DOI: 10.1111/j.1600-0765.2012.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential vanilloid‐1 regulates osteoprotegerin/RANKL homeostasis in human periodontal ligament cells

Abstract: Our study demonstrates that activation of TRPV1 leads to an increase of the OPG/RANKL ratio in HPDL cells. These findings suggest the novel function of TRPV1 in periodontal tissues, at least, as the regulator of the OPG/RANKL axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…Nevertheless, in our research, we found that blocking TRPV1 in the parodontium could reduce the expression of TRPV1 in the TG. Previous research showed that TRPV1 was present in gingival epithelial cells and periodontal ligament cells, and contributes to the regulation of cell proliferation and protein secretion [24][25]. Furthermore, suppressing TRPV1 also decreased the secretion of IL-1β in the gingival crevicular fluid.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, in our research, we found that blocking TRPV1 in the parodontium could reduce the expression of TRPV1 in the TG. Previous research showed that TRPV1 was present in gingival epithelial cells and periodontal ligament cells, and contributes to the regulation of cell proliferation and protein secretion [24][25]. Furthermore, suppressing TRPV1 also decreased the secretion of IL-1β in the gingival crevicular fluid.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, AEA but not 2-AG is known to activate transient receptor potential vanilloid type-1 receptor (TRPV1) [41]. Recent study shows that this receptor is expressed in hPdLC and might be activated by AEA [42]. Moreover, ablation of TRPV1 in mice results in exacerbated inflammatory response during endotoxic shock [43], which also suggests the role of this receptor in LPS-induced signaling.…”
Section: Discussionmentioning
confidence: 99%
“…This could potentially be explained if iron overload in TM prevents TRPV1 activation from further modifying TRAP levels -which are directly regulated by iron at the gene transcription level. 48 Indeed, TRAP is an iron phosphatase, thus the presence of iron overload, which is characteristic of patients with TM, may activate TRAP transcription per se. On the other hand, the activation of TRAP protein is associated with proteolytic cleavage in an exposed loop domain due to cathepsin K, 23 which was found to be significantly decreased in resiniferatoxin-treated TM-derived osteoclasts ( Figure 3A).…”
Section: Discussionmentioning
confidence: 99%